Antibacterial and anti-inflammatory activity of plant species used in traditional poultry ethnomedicine in Zimbabwe: A first step to developing alternatives to antibiotic poultry feed additives. (10th January 2023) - Jambwa, P.; Nkadimeng, S.M.; Mudimba, T.N.; Matope, G.; McGaw, L.J.
Abstract: Ethnopharmacological relevance: Global interest in phytogenic feed additives as alternatives to antibiotics in feed has been spurred by the banning of antibiotic growth promoters by several countries. Suitable plant extracts for development of phytogenic feed additives should have therapeutic value and should also be safe. Aim of study: The aim of this study was to evaluate the antibacterial, antioxidant and anti-lipoxygenase activities as well as cytotoxicity of selected plant species used in poultry ethnomedicine in Zimbabwe. Methods: Antibacterial activity was determined against three ATCC strains ( Staphylococcus aureus, Escherichia coli, Salmonella Enteritidis) and two clinical strains isolated from chickens ( Escherichia coli and Salmonella Gallinarum) using a two-fold serial microdilution assay. Qualitative antibacterial bioautography was also carried out using the ATCC strains. Antioxidant activities of crude acetone and methanol extracts were determined using free radical scavenging assays whilst anti-lipoxygenase activity was evaluated using a ferrous oxidation-xylenol orange (FOX) assay. Cytotoxicity was evaluated using a tetrazolium-based colorimetric assay (MTT assay) on Vero monkey kidney cells. Results: Erythrina abyssinica had the best antibacterial activity against both ATCC strains and clinical strains with minimum inhibitory concentration (MIC) values ranging from 0.02 to 0.156 mg/ml. Aloe greatheadii, Adenia gummifera (leaves), Senna singueana and Aloe chabaudii had moderate activity against the poultry pathogens. Bioautography showed that all ten plant species have antibacterial activity against the tested microorganisms with E. abyssinica and S. singueana having prominent bands of inhibition against both Gram-negative and Gram-positive bacteria. The acetone extract of S. singueana and the methanol extract of Euphorbia matabelensis had the most powerful antioxidant activities with mean IC50 values of 1.43 μg/ml and 1.31 μg/ml respectively in the ABTS assay which were comparable with those of the positive controls (ascorbic acid and trolox). Bobgunnia madagascariensis, A. chabaudii, E. abyssinica and Tridactyle bicaudata extracts had reasonable antioxidant activity. The S. singueana extract had the most potent anti-lipoxygenase activity with a mean IC50 value of 1.72 μg/ml. The cytotoxicity results showed that only the acetone extracts of A. greatheadii and S. singueana were relatively safe at concentrations that were active against the tested microorganisms (selective index >1). Regarding anti-lipoxygenase activity, extracts of B. madagascariensis, S. singueana, T. bicaudata and E. matabelensis were more active than toxic (selective index >5) indicating anti-inflammatory potential. Conclusions: This study showed that S. singueana had a cocktail of therapeutic activity and supports further investigation of this plant species for development of phytogenic poultry feed additives. Other plant species with noteworthy biological activities include B. madagascariensis, E. abyssinica, A. greatheadii, T. bicaudata and E. matabelensis . Graphical abstract: Image 1 Highlights: Several plant species are used in poultry ethnomedicine in Zimbabwe. Extracts of selected plants had promising antibacterial activity against chicken pathogens. Good selectivity index values and other useful bioactivities encourage further research. Plants may be a useful source of antibiotic feed additive alternatives in poultry.